The mechanism of first raindrops formation in deep convective clouds. Issue 16 (22nd August 2013) - Khain, A.; Prabha, Thara V.; Benmoshe, Nir; Pandithurai, G.; Ovchinnikov, M.
Abstract: [1] The formation of first raindrops in deep convective clouds is investigated. A combination of observational data analysis and 2D and 3D simulations of deep convective clouds suggests that the first raindrops form at the top of undiluted or slightly diluted cores. It is shown that droplet size distributions in these regions are wider and contain more large droplets than in diluted volumes. The results of the study suggest that the initial raindrop formation is determined by the basic microphysical processes within ascending adiabatic volumes. It allows one to predict the height of the formation of first raindrops considering the processes of cloud condensation nuclei activation, droplet diffusion growth, and coalescence growth. The results obtained in the study explain observational results through which the in‐cloud height of first raindrop formation depends linearly on the droplet number concentration at cloud base. The results also explain why a simple adiabatic parcel model can reproduce this dependence. The present study provides a physical basis for retrieval algorithms of cloud microphysical properties and aerosol properties using satellites. The study indicates that the role of mixing and entrainment in the formation of the first raindrops is not of crucial importance. It is also shown that low variability of effective and mean volume radii along horizontal traverses, as regularly observed by in situ measurements, can be simulated by high‐resolution cloud models in which mixing is parameterized by a traditional 1.5 order turbulence closure scheme. Key Points: raindrops form in slightly diluted cloudy volumes at the tops of bubble cores DSDs in non‐diluted DSDs in undiluted cores contain more large droplets entrainment is not of crucial importance in the formation of first raindrops